Evaluación de la aplicación de dos enmiendas orgánicas en tres dosis en la etapa de renovación en el cultivo de Mandarina (Citrus reticulata blanco) establecida en la zona de San Rafael, provincia del Carchi. - Chamorro Ortiz, Washington Eisenhower (2015)
This research evaluation of the application of two organic amendments in three doses at the stage of renewal in a culture of mandarin (Citrus reticulata) Established in the San Rafael, Carchi province, took place on the property of Mr. Raul Chamorro, Bolivar canton San Rafael parish, Esmeraldas area with an altitude of 2500 m and a temperature of 13.8 ° C. Block design was used completely at random (DBCA), with seven treatments and three repetitions factorial arrangement AxB + 1, where A corresponds to the amendments, B corresponds to the dose, but a witness without application. At work two factors were evaluated: 2 amendments; natural humus prepared based on bovinaza..........